Pathologic Changes Observed in Wild-Caught African Giant Rats (Cricetomys gambianus) from Kwali Area Council, Abuja, Nigeria - Oremeyi, Tenuche Zaynab; Adebayo, Sulaiman Abdul-Razaq; Christiana, Olajimbiti Ololade; Idoko , Idoko Sunday; Enejo, Abalaka Samson; Abdulazeez, Sani Nuhu; Edmond, Onije; Benjamin, Emikpe Obukowho; Onyemaechi, Egwu Godwin (Media Kedokteran Hewan, 2026)
The domestication of African giant rat (AGRs) is increasing due to its nutritional, economic, and biomedical value, but is constrained by infectious, metabolic, and degenerative diseases. This study assessed organ pathology in wild-captured AGRs to establish baseline health data for improved care and domestication. Forty (40) wild AGRs captured from Kwali (Nigeria), were euthanized for examination. Whole blood and serum samples (5 mL and 2 mL, respectively) were collected for hematological and biochemical analyses. Hearts, lungs, liver, and kidneys were harvested for gross and histopathological evaluations using standard techniques. No significant sex-based differences were observed in hematological or biochemical parameters. Lesions were present in 45% of the specimens, with the lungs being most affected, followed by the liver and kidneys. Pulmonary lesions were characterized by red hepatization and varied in pattern, ranging from interstitial to bronchointerstitial and broncho-pneumonia. Hepatic lesions included granulomatous, necrotizing, and lymphocytic hepatitis, with Capillaria hepatica ova observed in granulomatous cases. Renal lesions comprised focal infarctions, tubular epithelial degeneration, and multifocal necrosis. These findings underscore the underlying health challenges faced by wild African giant rats and highlight the zoonotic significance of Capillaria hepatica, emphasizing the need for vigilant surveillance to safeguard both animal and public health.